Nonaqueous electrolyte secondary battery
By attaching sulfonic acid compounds to the positive electrode active substance of the nonaqueous electrolyte secondary battery and setting the negative electrode mixture layer into a two-layer structure, adjusting the ratio of graphite particles, the problem in the prior art is difficult to achieve high capacity and excellent charge and discharge cycle characteristics at the same time, and achieving efficient battery performance.
Patent Information
- Application Number
- CN202380066547.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-09-28
- Filing Date
- 2023-08-03
- Publication Date
- 2025-04-25
AI Technical Summary
The prior art is difficult to achieve high capacity and excellent charge and discharge cycle characteristics simultaneously in non-aqueous electrolyte secondary batteries.
By attaching a sulfonic acid compound to the surface of the lithium-containing composite oxide particles of the positive electrode active material and setting the negative electrode mixture layer to a two-layer structure, the internal porosity of the first graphite particles is low and the internal porosity of the second graphite particles is high, the ratio of the first and second graphite particles is adjusted to ensure the non-aqueous electrolyte path in the negative electrode mixture layer.
While achieving high capacity, the charge and discharge cycle characteristics are improved, ensuring that the non-aqueous electrolyte path in the negative electrode mixture layer can be maintained even in the case of a deep charge and discharge depth.
Smart Images

Figure CN119895610A_ABST
Abstract
Description
Technical Field
[0001] The present disclosure relates to a nonaqueous electrolyte secondary battery. Background Art
[0002] Patent Document 1 proposes an active material which is 4 Ti 5 O 12 A surface layer containing a lithium sulfonate compound is formed on the surface of particles of lithium titanate as a main component. Patent Document 1 states that by using this active material in a negative electrode active material, a change in resistance before and after charge storage of a battery can be suppressed.
[0003] Prior art literature
[0004] Patent Literature
[0005] Patent Document 1: Japanese Patent Application Publication No. 2018-6164 Summary of the invention
[0006] In non-aqueous electrolyte secondary batteries, it is an important issue to improve charge-discharge cycle characteristics while ensuring high capacity. Conventional technologies including Patent Document 1 cannot fully address such issues and there is still much room for improvement.
[0007] The nonaqueous electrolyte secondary battery disclosed in the present invention comprises a positive electrode, a negative electrode and a nonaqueous electrolyte, wherein the positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide, wherein the sulfonic acid compound is a compound represented by formula (I), and the negative electrode comprises a negative electrode core and a negative electrode mixture layer disposed on the surface of the negative electrode core, wherein the negative electrode mixture layer comprises first graphite particles having an internal porosity of less than 5% and second graphite particles having an internal porosity of greater than 8% and less than 20%, and has a nonaqueous electrolyte. The first negative electrode mixture layer opposite to the core body, and the second negative electrode mixture layer opposite to the positive electrode, the thickness T1 of the first negative electrode mixture layer and the thickness T2 of the second negative electrode mixture layer satisfy 0.1≤T1 / (T1+T2)≤0.9, the ratio C1 of the first graphite particles in the first negative electrode mixture layer to the total mass of the first graphite particles and the second graphite particles and the ratio C2 of the first graphite particles in the second negative electrode mixture layer to the total mass of the first graphite particles and the second graphite particles satisfy C1<C2.
[0008]
[0009] (In formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0010] The nonaqueous electrolyte secondary battery disclosed herein has a high capacity and is excellent in charge and discharge cycle characteristics. BRIEF DESCRIPTION OF THE DRAWINGS
[0011] Figure 1 It is a cross-sectional view of a nonaqueous electrolyte secondary battery as an example of the embodiment.
[0012] Figure 2 It is a cross-sectional view of a negative electrode in one example of the embodiment.
[0013] Figure 3 This is a cross-sectional view of a graphite particle in one example of the embodiment. DETAILED DESCRIPTION
[0014] Even if the lithium titanate described in Patent Document 1 is used for the positive electrode, the reaction potential is low and the battery capacity is also reduced. The research results of the present inventors show that by making the sulfonic acid compound shown in the above formula (I) present on the particle surface of the lithium-containing composite oxide used as the positive electrode active material, a high-capacity and low-resistance non-aqueous electrolyte secondary battery can be achieved. It is believed that the reason is that the reaction resistance in the positive electrode is reduced by the function of the sulfonic acid compound, and the charge and discharge depth can be deepened. However, as the charge and discharge depth deepens due to the reduction in reaction resistance, a new issue of reduced charge and discharge cycle characteristics is generated. It is speculated that the reason is that as the charge and discharge depth deepens, the volume change of the negative electrode becomes larger, and the supply of non-aqueous electrolyte in the negative electrode mixture layer is insufficient.
[0015] Therefore, the inventors of the present invention have conducted further in-depth research, using a lithium-containing composite oxide with a specific sulfonic acid compound attached to the surface of the particles as the positive electrode active material, while setting the negative electrode mixture layer to a two-layer structure, so that the proportion of the first graphite particles with low internal porosity in the second negative electrode mixture layer on the surface side is greater than the proportion of the first graphite particles with low internal porosity in the first negative electrode mixture layer on the core side, thereby successfully ensuring high capacity and improving the charge and discharge cycle characteristics. According to the non-aqueous electrolyte secondary battery disclosed in the present invention, it is believed that even in the case of a deep charge and discharge depth, the path of the non-aqueous electrolyte in the negative electrode mixture layer can be ensured, so the charge and discharge cycle characteristics are improved. The negative electrode mixture layer is made by rolling the coating, but the first graphite particles are less likely to break during rolling than the second graphite particles. It is speculated that by including a large amount of the first graphite particles in the second negative electrode mixture layer, the path of the non-aqueous electrolyte in the negative electrode mixture layer 32 can be ensured.
[0016] Hereinafter, an example of an embodiment of the non-aqueous electrolyte secondary battery disclosed in the present invention will be described in detail with reference to the accompanying drawings. It should be noted that the configuration formed by selectively combining the various structural features of the multiple embodiments and modified examples described below is included in the scope of the present invention. It should be noted that in this specification, "~" refers to a range including the upper and lower limits before and after "~".
[0017] Hereinafter, as a non-aqueous electrolyte secondary battery, a cylindrical battery in which a wound electrode body 14 is housed in an outer can 16 having a bottomed cylindrical shape is exemplified, but the outer shell of the battery is not limited to a cylindrical outer can. The non-aqueous electrolyte secondary battery disclosed herein may be, for example, a square battery having a square outer can, a coin-shaped battery having a coin-shaped outer can, or a bag-shaped battery having an outer shell composed of a laminate sheet including a metal layer and a resin layer. In addition, the electrode body is not limited to a wound type, and may also be a stacked electrode body in which a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with a separator.
[0018] Figure 1 FIG. 1 is a cross-sectional view of a nonaqueous electrolyte secondary battery 10 as an example of an embodiment. Figure 1 As shown, the nonaqueous electrolyte secondary battery 10 includes a wound electrode body 14, a nonaqueous electrolyte, and an outer can 16 for storing the electrode body 14 and the nonaqueous electrolyte. The electrode body 14 includes a positive electrode 11, a negative electrode 12, and a separator 13, and has a wound structure in which the positive electrode 11 and the negative electrode 12 are wound in a spiral shape with the separator 13 interposed therebetween. The outer can 16 is a metal container in a bottomed cylindrical shape with one end side open in the axial direction, and the opening of the outer can 16 is blocked by a sealing body 17. In the following, for convenience of description, the sealing body 17 side of the battery is set as the upper side, and the bottom side of the outer can 16 is set as the lower side.
[0019] The non-aqueous electrolyte has lithium ion conductivity. The non-aqueous electrolyte includes a non-aqueous solvent and an electrolyte salt dissolved in the non-aqueous solvent. Examples of the non-aqueous solvent include esters, ethers, nitriles, amides, and mixed solvents of two or more thereof. Examples of the non-aqueous solvent include ethylene carbonate (EC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), diethyl carbonate (DEC), and mixed solvents thereof. The non-aqueous solvent may also contain a halogen-substituted product (e.g., fluoroethylene carbonate, etc.) in which at least a portion of the hydrogen atoms of these solvents are replaced by halogen atoms such as fluorine. For example, LiPF is used as the electrolyte salt. 6 And other lithium salts.
[0020] The positive electrode 11, the negative electrode 12, and the separator 13 constituting the electrode body 14 are all strip-shaped long bodies, and are alternately stacked in the radial direction of the electrode body 14 by being wound into a spiral shape. The negative electrode 12 is formed to be one circle larger than the positive electrode 11 to prevent the precipitation of lithium. That is, the negative electrode 12 is formed longer than the positive electrode 11 in the length direction and the width direction. The separator 13 is formed to be at least one circle larger than the positive electrode 11, for example, two sheets are arranged in a manner of clamping the positive electrode 11. The electrode body 14 has a positive electrode lead 20 connected to the positive electrode 11 by welding or the like, and a negative electrode lead 21 connected to the negative electrode 12 by welding or the like.
[0021] Insulating plates 18 and 19 are disposed above and below the electrode body 14 , respectively. Figure 1 In the example shown, the positive electrode lead 20 extends to the sealing body 17 side through the through hole of the insulating plate 18, and the negative electrode lead 21 extends to the bottom side of the outer can 16 through the outer side of the insulating plate 19. The positive electrode lead 20 is connected to the lower surface of the internal terminal plate 23 of the sealing body 17 by welding or the like, and the top plate of the sealing body 17, that is, the cover 27 electrically connected to the internal terminal plate 23 serves as the positive terminal. The negative electrode lead 21 is connected to the bottom inner surface of the outer can 16 by welding or the like, and the outer can 16 serves as the negative terminal.
[0022] A gasket 28 is provided between the outer can 16 and the sealing body 17 to ensure the airtightness inside the battery. A groove portion 22 is formed on the outer can 16, in which a part of the side portion protrudes inward and supports the sealing body 17. The groove portion 22 is preferably formed in an annular shape along the circumferential direction of the outer can 16, and the sealing body 17 is supported by its upper surface. The sealing body 17 is fixed to the upper part of the outer can 16 through the groove portion 22 and the open end of the outer can 16 that tightens the sealing body 17.
[0023] The sealing body 17 has a structure in which an internal terminal plate 23, a lower valve body 24, an insulating member 25, an upper valve body 26 and a cover 27 are stacked in order from the electrode body 14 side. The components constituting the sealing body 17 have, for example, a disc shape or a ring shape, and the components except the insulating member 25 are electrically connected to each other. The lower valve body 24 and the upper valve body 26 are connected at their respective central portions, and an insulating member 25 is sandwiched between their respective peripheral portions. When the internal pressure of the battery rises due to abnormal heat release, the lower valve body 24 is deformed and broken in a manner that pushes the upper valve body 26 toward the cover 27 side, thereby cutting off the current path between the lower valve body 24 and the upper valve body 26. When the internal pressure rises further, the upper valve body 26 breaks, and the gas is discharged from the opening of the cover 27.
[0024] Hereinafter, the positive electrode 11 , the negative electrode 12 , and the separator 13 constituting the electrode body 14 , in particular, the positive electrode active material constituting the positive electrode 11 and the negative electrode active material constituting the negative electrode 12 will be described in detail.
[0025] [positive electrode]
[0026] The positive electrode 11, for example, has a positive electrode core and a positive electrode mixture layer disposed on the surface of the positive electrode core. The positive electrode core can be made of a foil of a metal such as aluminum that is stable within the potential range of the positive electrode 11, a thin film of the metal disposed on the surface, or the like. The positive electrode mixture layer contains a positive electrode active material, a conductive agent, and a binder, and is preferably disposed on both sides of the positive electrode core except for the portion connected to the positive electrode lead 20. The positive electrode 11 can be manufactured, for example, by applying a positive electrode mixture slurry containing a positive electrode active material, a conductive agent, and a binder to the surface of the positive electrode core, drying the coating, and then compressing it to form a positive electrode mixture layer on both sides of the positive electrode core.
[0027] As the conductive agent contained in the positive electrode mixture layer, carbon black such as acetylene black and ketjen black, graphite, carbon nanotubes (CNT), carbon nanofibers, graphene and other carbon materials can be exemplified. As the binder contained in the positive electrode mixture layer, fluorine-containing resins such as polytetrafluoroethylene (PTFE) and polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, polyolefin, etc. can be exemplified. In addition, these resins can be used in combination with carboxymethyl cellulose (CMC) or its salt, polyethylene oxide, etc. The content of the conductive agent and the binder is, for example, 0.1% by mass or more and 5% by mass or less relative to the mass of the positive electrode mixture layer.
[0028] The positive electrode 11 includes a lithium-containing composite oxide and a sulfonic acid compound present on the surface of the composite oxide particles. The lithium-containing composite oxide with the sulfonic acid compound attached to the particle surface functions as a positive electrode active material. The sulfonic acid compound is a compound represented by formula (I).
[0029]
[0030] In formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
[0031] The sulfonic acid compound represented by formula (I) (hereinafter sometimes simply referred to as "sulfonic acid compound") reduces the reaction resistance in positive electrode 11 and improves the output characteristics of the battery. In addition, as the resistance is reduced, the depth of charge and discharge can be increased, and the capacity can be increased.
[0032] From the viewpoint of increasing the capacity, the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is preferably 0.1% by mass or more and 1% by mass or less relative to the mass of the lithium-containing composite oxide.
[0033] The positive electrode active material may be mainly composed of composite particles of lithium-containing composite oxides with sulfonic acid compounds attached to the particle surface, and may be substantially composed of the composite particles. It should be noted that the positive electrode active material may also contain composite oxides or other compounds other than the composite particles within the scope of not impairing the purpose of the present disclosure.
[0034] The lithium-containing composite oxide preferably has a layered rock salt structure. As the layered rock salt structure of the lithium-containing composite oxide, for example, a layered rock salt structure belonging to the space group R-3m, a layered rock salt structure belonging to the space group C2 / m, etc. can be cited. Among them, from the viewpoint of high capacity and stability of the crystal structure, a layered rock salt structure belonging to the space group R-3m is preferred. The layered rock salt structure of the lithium-containing composite oxide includes a transition metal layer, a Li layer and an oxygen layer.
[0035] The lithium-containing composite oxide is a composite oxide containing metal elements such as Ni, Co, Al, and Mn in addition to Li. The metal elements constituting the lithium-containing composite oxide are, for example, Ni, Co, and M (M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn). Among them, it is preferred to contain at least one selected from Ni, Co, Al, and Mn. As an example of a suitable composite oxide, a composite oxide containing Ni, Co, and Al and a composite oxide containing Ni, Co, and Mn can be cited.
[0036] From the viewpoint of high capacity, the lithium-containing composite oxide preferably contains 80 mol% or more of Ni relative to the total molar number of metal elements other than Li. In addition, the effect of adding the sulfonic acid compound is more significant when a lithium-containing composite oxide with a high Ni content is used. The Ni content relative to the total molar number of metal elements other than Li can be 87 mol% or more, or 90 mol% or more. The upper limit of the Ni content is, for example, 95 mol%.
[0037] As described above, an example of a suitable lithium-containing composite oxide is a composite oxide containing Ni, Co and M. Relative to the total molar number of metal elements other than Li, the content of Co is, for example, 0 mol% or more and 20 mol% or less. Relative to the total molar number of metal elements other than Li, the content of M is, for example, 0 mol% or more and 20 mol% or less. Co may not be substantially added, and by adding a small amount of Co, the battery performance is improved. M preferably includes at least one of Mn and Al.
[0038] For example, lithium-containing composite oxides are composed of the general formula Li a Ni x Co y M z O 2-b (wherein, 0.95≤a≤1.2, 0.80≤x≤0.95, 0≤y≤0.20, 0≤z≤0.20, 0≤b≤0.05, x+y+z=1, and M is at least one element selected from the group consisting of Al, Mn, Fe, Ti, Si, Nb, Mo, W, and Zn). Preferably, x in the above general formula is 0.87≤x≤0.95.
[0039] The content of elements constituting the lithium-containing composite oxide can be measured using an inductively coupled plasma atomic emission spectrometer (ICP-AES), an electron probe microanalyzer (EPMA), an energy dispersive X-ray analyzer (EDX), or the like.
[0040] The lithium-containing composite oxide is, for example, a secondary particle formed by the aggregation of multiple primary particles. The volume-based median particle size (D50) of the composite oxide is not particularly limited, and as an example, is 3 μm or more and 30 μm or less, preferably 5 μm or more and 25 μm or less. In the case where the composite oxide is a secondary particle formed by the aggregation of primary particles, the D50 of the composite oxide refers to the D50 of the secondary particle. D50 refers to the particle size at which the cumulative frequency from the smaller particle size in the volume-based particle size distribution becomes 50%, also known as the median diameter. The particle size distribution of the composite oxide (the same is true for the negative electrode active material) is measured using a laser diffraction particle size distribution measuring device (for example, MT3000II manufactured by MICROTRAC BELL INC.) and water as the dispersion medium.
[0041] The average particle size of primary particles constituting the lithium-containing composite oxide is, for example, 0.05 μm to 1 μm. The average particle size of the primary particles is calculated by averaging the diameters of the circumscribed circles of the primary particles extracted by analyzing a scanning electron microscope (SEM) image of a cross section of the secondary particles.
[0042] As described above, the sulfonic acid compound present on the surface of the particles of the lithium-containing composite oxide is a compound represented by formula (I).
[0043]
[0044] In formula (I), A is an element of Group 1 or Group 2, R is a hydrocarbon group, and n is 1 or 2. A is preferably an element of Group 1. Among them, Li or Na is more preferred, and Li is particularly preferred.
[0045] In formula (I), R is preferably an alkyl group. The carbon number of the alkyl group is preferably 5 or less, more preferably 3 or less. From the viewpoint of reducing the reaction resistance, an example of a suitable R is an alkyl group having a carbon number of 3 or less, wherein a methyl group is preferred. It should be noted that in R, a portion of the hydrogen bonded to the carbon may be substituted by fluorine. In addition, n in formula (I) is preferably 1.
[0046] Specific examples of the sulfonic acid compound include lithium methanesulfonate, lithium ethanesulfonate, lithium propanesulfonate, sodium methanesulfonate, sodium ethanesulfonate, magnesium methanesulfonate, lithium fluoromethanesulfonate, etc. Among them, at least one selected from the group consisting of lithium methanesulfonate, lithium ethanesulfonate and sodium methanesulfonate is preferred, and lithium methanesulfonate is particularly preferred.
[0047] The sulfonic acid compound is present, for example, homogeneously on the entire surface of the particles of the lithium-containing composite oxide. The presence of the sulfonic acid compound on the surface of the particles of the lithium-containing composite oxide can be confirmed by Fourier transform infrared spectroscopy (FT-IR). In the infrared absorption spectrum obtained by FT-IR, the positive electrode active material containing lithium methanesulfonate, for example, has a peak at 1238 cm -1 、1175cm-1 、1065cm -1 、785cm -1 There is an absorption peak near 1238cm -1 、1175cm -1 、1065cm -1 The peaks near 785cm are caused by the SO stretching vibration of lithium methanesulfonate. -1 The nearby peaks are peaks derived from CS stretching vibration of lithium methanesulfonate.
[0048] For positive electrode active materials containing sulfonic acid compounds other than lithium methanesulfonate, the presence can be confirmed by the absorption peak derived from the sulfonic acid compound in the infrared absorption spectrum. It should be noted that the presence of the sulfonic acid compound on the surface of the particles of the lithium-containing composite oxide can be confirmed by ICP, atomic absorption spectroscopy, X-ray photoelectron spectroscopy (XPS), radioactive light XRD measurement, TOF-SIMS, etc.
[0049] The positive electrode active material as an example of the embodiment can be produced by the following method. It should be noted that the production method described here is an example, and the production method of the positive electrode active material is not limited to this method.
[0050] First, a metal oxide containing metal elements such as Ni, Co, Al, and Mn is synthesized. Then, the metal oxide and a lithium compound are mixed and calcined to obtain a lithium-containing composite oxide. The metal oxide is synthesized, for example, by stirring a solution of a metal salt containing Ni, Co, Al, Mn, etc. while dropping an alkaline solution such as sodium hydroxide, adjusting the pH to the alkaline side (for example, 8.5 to 12.5), thereby precipitating a composite hydroxide containing metal elements such as Ni, Co, Al, and Mn (coprecipitation), and heat-treating the composite hydroxide to synthesize the metal oxide. The heat treatment temperature is not particularly limited, and as an example, it is 300°C to 600°C.
[0051] Examples of lithium compounds include Li 2 CO 3 、LiOH、Li 2 O 2 , Li 2 O、LiNO 3 、LiNO 2 , Li 2 SO 4 、LiOH·H 2O, LiH, LiF, etc. The metal oxide and the lithium compound are mixed, for example, in a molar ratio of the metal element in the metal oxide to Li in the lithium compound of 1:0.98 to 1:1.1. It should be noted that when mixing the metal oxide and the lithium compound, other metal raw materials may be added as needed.
[0052] The mixture of the metal oxide and the lithium compound is calcined, for example, in an oxygen atmosphere. The mixture can be calcined through multiple temperature rising processes. The calcining process includes: a first temperature rising process of heating to 450°C to 680°C at a temperature rising rate of, for example, 1.0°C / min to 5.5°C / min, and a second temperature rising process of heating to a temperature exceeding 680°C at a temperature rising rate of 0.1°C / min to 3.5°C / min. The maximum reaching temperature of the calcining process can be set to 700°C to 850°C, and can be maintained at this temperature for 1 hour to 10 hours.
[0053] Next, the calcined product (containing lithium composite oxide) is washed with water and dehydrated to obtain a cake-like composition. The residual alkali component is removed by this washing process. The washing and dehydration can be carried out by existing known methods. Next, the cake-like composition is dried to obtain a powdery composition. The drying process can be carried out under a vacuum atmosphere. An example of drying conditions is 0.5 hours to 15 hours at a temperature of 150°C to 400°C.
[0054] The sulfonic acid compound is added to the cake-like composition obtained in the washing step, for example, or to the powder-like composition obtained in the drying step. In this case, a sulfonic acid solution may be added instead of the sulfonic acid compound or together with the sulfonic acid compound. Thus, a positive electrode active material having a sulfonic acid compound attached to the surface of particles of the lithium-containing composite oxide can be obtained. The sulfonic acid compound may be added as an aqueous dispersion. In addition, the sulfonic acid solution is preferably an aqueous solution of sulfonic acid. The concentration of sulfonic acid in the sulfonic acid solution is, for example, 0.5% by mass or more and 40% by mass or less.
[0055] Note that, since a certain amount of lithium compound remains in the cake-like composition, by adding the sulfonic acid solution to the cake-like composition, Li dissolved in water in the cake reacts with the sulfonic acid to obtain lithium sulfonate.
[0056] [negative electrode]
[0057] Figure 2 1 is a cross-sectional view of a negative electrode 12 in one embodiment. Figure 2 As shown, the negative electrode 12 includes a negative electrode core 30 and a negative electrode mixture layer 32 disposed on the surface of the negative electrode core 30. The negative electrode mixture layer 32 includes a first negative electrode mixture layer 32a facing the negative electrode core 30 and a second negative electrode mixture layer 32b facing the positive electrode 11.
[0058] The thickness T1 of the first negative electrode mixture layer 32a and the thickness T2 of the second negative electrode mixture layer 32b satisfy 0.1≤T1 / (T1+T2)≤0.9. When T1 / (T1+T2)<0.1 or T1 / (T1+T2)>0.9, the charge-discharge cycle characteristics deteriorate. T1 and T2 preferably satisfy 0.5≤T1 / (T1+T2)≤0.75. In this case, the improvement of the charge-discharge cycle characteristics of the secondary battery 10 is more significant.
[0059] The negative electrode core 30 may be made of a foil of a metal such as copper that is stable within the potential range of the negative electrode 12, or a thin film having the metal disposed on the surface. The negative electrode mixture layer 32 includes first graphite particles having an internal porosity of 5% or less, and second graphite particles having an internal porosity of 8% or more and 20% or less. The negative electrode mixture layer 32 is preferably provided on both surfaces of the negative electrode core 30 except for the portion connected to the negative electrode lead 21.
[0060] The first graphite particles and the second graphite particles are not particularly limited and may be natural graphite, artificial graphite or the like, but artificial graphite is preferred from the viewpoint of easy adjustment of the internal porosity or the like.
[0061] For the determination method of the internal porosity of graphite particles, refer to Figure 3 While explaining. Figure 3 : is a cross-sectional view of a graphite particle 40 contained in the negative electrode mixture layer 32. When viewed from the cross section of the graphite particle 40, the graphite particle 40 has closed pores 42 (hereinafter referred to as internal pores 42) that are not connected from the inside of the particle to the particle surface, and pores 44 (hereinafter referred to as external pores 44) that are connected from the inside of the particle to the particle surface. The internal porosity of the graphite particle 40 is obtained by the following steps.
[0062] <Method for measuring internal porosity>
[0063] (1) Exposing the cross section of the negative electrode mixture layer 32. As a method for exposing the cross section, for example, a part of the negative electrode 12 is cut and processed using an ion milling device (for example, IM4000PLUS manufactured by Hitachi High-Tech Corporation) to expose the cross section of the negative electrode mixture layer 32.
[0064] (2) Using a scanning electron microscope, a reflected electron image of the cross section of the exposed negative electrode mixture layer 32 is taken. The magnification for taking the reflected electron image is 3,000 to 5,000 times.
[0065] (3) The cross-sectional image obtained above is imported into a computer and binarized using image analysis software (e.g., ImageJ manufactured by the National Institutes of Health, U.S.A.) to obtain a binary processed image in which the particle cross section in the cross-sectional image is converted to black and the pores existing in the particle cross section are converted to white.
[0066] (4) From the binary processed image, graphite particles 40 with a particle size of 5 μm to 50 μm are selected, and the area of the cross section of the graphite particles and the area of the internal pores 42 existing in the cross section of the graphite particles are calculated. Here, the area of the cross section of the graphite particles refers to the area of the region surrounded by the periphery of the graphite particles 40, that is, the area of the entire cross section of the graphite particles 40. In addition, among the pores existing in the cross section of the graphite particles, pores with a width of 3 μm or less are sometimes difficult to judge whether they are internal pores 42 or external pores 44 in image analysis. Therefore, pores with a width of 3 μm or less can be regarded as internal pores 42. Then, based on the calculated area of the cross section of the graphite particles and the area of the internal pores 42 in the cross section of the graphite particles, the internal porosity of the graphite particles 40 is calculated (area of the internal pores 42 in the cross section of the graphite particles × 100 / area of the cross section of the graphite particles). The internal porosity of the first graphite particles and the second graphite particles is an average value of ten first graphite particles and ten second graphite particles, respectively.
[0067] The first graphite particles and the second graphite particles are produced, for example, as follows.
[0068] <First graphite particles having an internal porosity of 5% or less>
[0069] For example, coke (precursor) as the main raw material is crushed to a specified size, and then sintered at a temperature of 2600°C or above to graphitize them in an aggregated state with an aggregating agent, and then sieved to obtain the first graphite particles of the desired size. Here, the internal porosity can be adjusted to less than 5% according to the particle size of the precursor after crushing, the particle size of the precursor in an aggregated state, etc. For example, the average particle size (median particle size D50) of the precursor after crushing is preferably in the range of 12μm to 25μm. In addition, if the internal porosity is to be further reduced within the range of less than 5%, it is preferred to increase the particle size of the precursor after crushing.
[0070] <Second graphite particles having an internal porosity of 8% to 20%>
[0071] For example, coke (precursor) as the main raw material is crushed to a specified size, aggregated with an aggregating agent, and then further pressed into a block state, fired at a temperature of 2600°C or above to graphitize it. The block-shaped body after graphitization is crushed and sieved to obtain a second graphite particle of a desired size. Here, the internal porosity can be adjusted to 8% to 20% by the amount of volatile components added to the block-shaped body. In the case where a part of the aggregating agent added to the coke (precursor) volatilizes during firing, the aggregating agent can be used as a volatile component. As such an aggregating agent, asphalt can be exemplified.
[0072] At least a portion of the surface of the first graphite particles may be covered with amorphous carbon. The first graphite particles are covered with amorphous carbon to improve electrical conductivity.
[0073] The ratio C1 of the first graphite particles to the total mass of the first and second graphite particles in the first negative electrode mixture layer 32a and the ratio C2 of the first graphite particles to the total mass of the first and second graphite particles in the second negative electrode mixture layer 32b satisfy C1<C2. Thus, the charge and discharge cycle characteristics of the secondary battery 10 are improved.
[0074] C1 preferably satisfies 20 mass % ≤ C1 ≤ 100 mass %, and more preferably satisfies 20 mass % ≤ C1 ≤ 80 mass %. This further significantly improves the charge-discharge cycle characteristics of the secondary battery 10. C2 satisfies, for example, 0 mass % ≤ C2 ≤ 80 mass %.
[0075] The negative electrode mixture layer 32 may contain negative electrode active materials other than the first graphite particles and the second graphite particles. Examples of negative electrode active materials other than graphite particles include silicon-containing materials. Examples of silicon-containing materials include Si, alloys containing Si, SiO x (x is 0.5 to 1.5) and other silicon oxides. Silicon-containing materials are negative electrode materials that can improve battery capacity more than the first graphite particles and the second graphite particles, but on the other hand, the volume expansion accompanying charge and discharge is large, so it is disadvantageous in terms of charge and discharge cycle characteristics. From the aspects of improving battery capacity and suppressing the reduction of charge and discharge cycle characteristics, the content of silicon-containing materials is preferably 1% to 10% by mass, and more preferably 3% to 7% by mass, relative to the total mass of the negative electrode active material. As negative electrode active materials other than silicon-containing materials, for example, metals alloyed with lithium such as tin (Sn), or alloys and oxides containing metal elements such as Sn can be listed. The content of materials other than the first graphite particles, the second graphite particles and the silicon-containing material is preferably less than 10% by mass, for example, relative to the total mass of the negative electrode active material.
[0076] The negative electrode mixture layer 32 may also contain a binder, a thickener, a conductive agent, etc. in addition to the negative electrode active material. As the binder contained in the negative electrode mixture layer 32, for example, fluororesins such as styrene-butadiene rubber (SBR), nitrile rubber (NBR), polytetrafluoroethylene (PTFE), polyvinylidene fluoride (PVDF), polyacrylonitrile (PAN), polyimide, acrylic resin, and polyolefin can be listed. Among these, SBR and NBR are preferred, and SBR is particularly preferred. These can be used alone or in combination of two or more. The binder contained in the first negative electrode mixture layer 32a and the binder contained in the second negative electrode mixture layer 32b can be different from each other, but are preferably the same.
[0077] As the thickener contained in the negative electrode mixture layer 32, for example, carboxymethyl cellulose (CMC) or its salt (CMC-Na, etc.), polyacrylic acid (PAA) or its salt (which can be PAA-Na, PAA-K, etc., or a partially neutralized salt), polyvinyl alcohol (PVA) can be listed. Among these, CMC or its salt is preferred. These can be used alone or in combination of two or more. The thickener contained in the first negative electrode mixture layer 32a and the thickener contained in the second negative electrode mixture layer 32b can be different from each other, but are preferably the same. As the conductive agent contained in the negative electrode mixture layer 32, for example, carbon nanotubes (CNTs) can be exemplified.
[0078] Next, the method for forming the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b is described. For example, first, the negative electrode active material, binder and solvent such as water contained in the first negative electrode mixture layer 32a are mixed to prepare the first negative electrode mixture slurry. Separately, the negative electrode active material, binder and solvent such as water contained in the second negative electrode mixture layer 32b are mixed to prepare the second negative electrode mixture slurry. The content of the first graphite particles in the second negative electrode mixture slurry is greater than the content of the first graphite particles in the first negative electrode mixture slurry. Then, after applying the first negative electrode mixture slurry on both sides of the negative electrode core and drying, the second negative electrode mixture slurry is applied to both sides on the coating film of the first negative electrode mixture slurry and dried. Furthermore, the coating film is rolled using a calendering roller, thereby forming the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b. It should be noted that in the above method, the second negative electrode mixture slurry is applied after the first negative electrode mixture slurry is applied and dried, but the second negative electrode mixture slurry may be applied before the first negative electrode mixture slurry is applied and dried. In addition, the second negative electrode mixture slurry may be applied on the first negative electrode mixture layer 32a after the first negative electrode mixture slurry is applied and dried and rolled. By changing the rolling conditions of the first negative electrode mixture layer 32a and the second negative electrode mixture layer 32b, the respective packing densities can be adjusted more freely.
[0079] [Separator]
[0080] The separator 13 uses a porous sheet with ion permeability and insulation. As specific examples of the porous sheet, microporous films, woven fabrics, nonwoven fabrics, etc. can be listed. As the material of the separator 13, polyolefins such as polyethylene and polypropylene, cellulose, etc. are suitable. The separator 13 can be a single-layer structure or a multi-layer structure. In addition, a resin layer with high heat resistance such as aramid resin can be formed on the surface of the separator 13.
[0081] A filler layer containing an inorganic filler may be formed at the interface between the separator 13 and at least one of the positive electrode 11 and the negative electrode 12. Examples of the inorganic filler include oxides containing metal elements such as Ti, Al, Si, and Mg, and phosphate compounds. The filler layer may be formed by applying a slurry containing the filler to the surface of the positive electrode 11, the negative electrode 12, or the separator 13.
[0082] Example
[0083] Hereinafter, the present disclosure will be further described based on examples, but the present disclosure is not limited to these examples.
[0084] <Example 1>
[0085] [Preparation of positive electrode active material]
[0086] The [Ni 0.90 Al 0.05 Mn 0.05 ](OH) 2 The composite hydroxide shown was calcined at 500°C for 8 hours to obtain an oxide (Ni 0.90 Al 0.05 Mn 0.05 O 2 Next, LiOH and the composite oxide were mixed so that the molar ratio of Li to the total amount of Ni, Al and Mn was 1.03:1 to obtain a mixture. The mixture was placed under an oxygen gas flow with an oxygen concentration of 95% (per 10 cm 3 The mixture was calcined at a rate of 2 mL / min and a flow rate of 5 L / min per kg of the mixture), from room temperature to 650°C at a heating rate of 2.0°C / min, and then from 650°C to 780°C at a heating rate of 0.5°C / min to obtain a lithium-containing composite oxide.
[0087] Water is added to the obtained lithium-containing composite oxide to make the slurry concentration become 1500g / L, stirred for 15 minutes, and filtered to obtain a cake-like composition. Powdered lithium methanesulfonate is added to the cake-like composition. The amount of lithium methanesulfonate added is 0.5% by mass relative to the total mass of the lithium-containing composite oxide. After adding lithium methanesulfonate, it is dried under a vacuum atmosphere at 180°C for 2 hours to obtain a positive electrode active material. It should be noted that the presence of lithium methanesulfonate on the particle surface of the composite oxide was confirmed by Fourier transform infrared spectroscopy (FT-IR).
[0088] [Production of positive electrode]
[0089] The positive electrode active material, acetylene black and polyvinylidene fluoride are mixed in a mass ratio of 98:1:1, and N-methyl-2-pyrrolidone (NMP) is used as a dispersion medium to prepare a positive electrode mixture slurry. Next, the positive electrode mixture slurry is applied to the positive electrode core formed by aluminum foil, and after the coating is dried and compressed, the positive electrode core is cut into a specified electrode size to obtain a positive electrode having a positive electrode mixture layer disposed on both sides of the positive electrode core. It should be noted that an exposed portion exposed on the surface of the positive electrode core is provided on a part of the positive electrode.
[0090] [Preparation of the first graphite particles]
[0091] The coke was crushed to an average particle size (median particle size D50) of 12 μm. Pitch was added as a binder to the crushed coke, and the coke was aggregated to an average particle size (median particle size D50) of 17 μm. The aggregate was sintered at a temperature of 2800° C. for graphitization, and then sieved using a 250-mesh sieve to obtain the first graphite particles with an average particle size (median particle size D50) of 23 μm.
[0092] [Production of the Second Graphite Particles]
[0093] The coke was pulverized to an average particle size (median particle size D50) of 15 μm, and pitch was added as a binder to the pulverized coke to aggregate it. Then, a 1.6 g / cm 3 ~1.9g / cm 3 The block molded body is sintered at a temperature of 2800°C for graphitization. Next, the graphitized block molded body is crushed and sieved using a 250-mesh sieve to obtain a second graphite particle having an average particle size (median particle size D50) of 23 μm.
[0094] [Production of negative electrode]
[0095] The first graphite particles are used as the first negative electrode active material. 100 parts by mass of the first negative electrode active material, 1 part by mass of styrene-butadiene rubber (SBR) and 1 part by mass of carboxymethyl cellulose (CMC) are mixed, and an appropriate amount of water is added to prepare a first negative electrode mixture slurry. In addition, the second graphite particles are used as the second negative electrode active material. 100 parts by mass of the second negative electrode active material, 1 part by mass of SBR and 1 part by mass of CMC are mixed, and an appropriate amount of water is added to prepare a second negative electrode mixture slurry.
[0096] The first negative electrode mixture slurry is applied to both sides of the negative electrode core formed by copper foil by a doctor blade method, and dried to form the first negative electrode mixture layer. Furthermore, the second negative electrode mixture slurry mentioned above is applied on the first negative electrode mixture layer, and dried to form the second negative electrode mixture layer. At this time, the coating mass ratio per unit area of the first negative electrode mixture slurry and the second negative electrode mixture slurry is set to 50:50. The first negative electrode mixture layer and the second negative electrode mixture layer are rolled by a calendering roller to produce a negative electrode. The value of T1 / (T1+T2) calculated from the thickness T1 of the first negative electrode mixture layer and the thickness T2 of the second negative electrode mixture layer of the prepared negative electrode is 0.5. It should be noted that an exposed portion exposed on the surface of the negative electrode core is provided in a part of the negative electrode. In addition, in the produced negative electrode, the internal porosity of the first graphite particles and the second graphite particles was measured, and the results were 3% and 15%, respectively.
[0097] [Preparation of non-aqueous electrolyte]
[0098] LiPF 6 The non-aqueous electrolyte was prepared by dissolving in a mixed solvent of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and dimethyl carbonate (DMC) at a volume ratio of 3:3:4 (25° C.) at a concentration of 1.2 mol / L.
[0099] [Production of test battery cell (secondary battery)]
[0100] Separately, an aluminum lead is installed on the exposed portion of the positive electrode, and a nickel lead is installed on the exposed portion of the negative electrode, and the positive electrode and the negative electrode are wound into a spiral shape through a polyolefin separator, thereby making a wound electrode body. Insulating plates are respectively arranged above and below the electrode body, and the electrode body is stored in an outer can. Separately, the negative electrode lead is welded to the bottom of the outer can with a bottomed cylindrical shape, and the positive electrode lead is welded to the sealing body. The electrolyte is injected into the outer can, and the opening of the outer can is sealed through the sealing body through the gasket to make a secondary battery as a test battery unit.
[0101] [Evaluation of initial discharge capacity and charge-discharge cycle characteristics (capacity retention rate after cycle test)]
[0102] For the above test battery cell, at a temperature of 25°C, charge at a constant current of 0.2C until the battery voltage reaches 4.2V, and then charge at a constant voltage of 4.2V until the current value reaches 0.02C. Then, discharge at a constant current of 0.2C until the battery voltage reaches 2.5V, and take the discharge capacity at this time as the initial discharge capacity. Take this charge and discharge as one cycle, perform 200 cycles, calculate the initial discharge capacity and the discharge capacity of the 200th cycle, and calculate the capacity retention rate according to the following formula. The larger the capacity retention rate, the better the charge and discharge cycle characteristics.
[0103] Capacity retention rate (%) = discharge capacity at the 200th cycle / initial discharge capacity × 100
[0104] <Comparative Example 1>
[0105] A test cell was produced and evaluated in the same manner as in Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0106] <Example 2>
[0107] In the preparation of the negative electrode, a test cell was prepared in the same manner as in Example 1 except that the first graphite particles and the second graphite particles were mixed at a mass ratio of 50:50 and this was used as the first negative electrode active material, and evaluation was performed.
[0108] <Comparative Example 2>
[0109] A test cell was produced and evaluated in the same manner as in Example 2 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0110] <Example 3>
[0111] In the preparation of the negative electrode, a test cell was prepared in the same manner as in Example 1 except that the first graphite particles and the second graphite particles were mixed at a mass ratio of 80:20 and this was used as the first negative electrode active material, and evaluation was performed.
[0112] <Comparative Example 3>
[0113] A test cell was produced and evaluated in the same manner as in Example 3 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0114] <Example 4>
[0115] In the preparation of the negative electrode, a test cell was prepared in the same manner as in Example 1 except that the first graphite particles and the second graphite particles were mixed at a mass ratio of 20:80 and this was used as the first negative electrode active material, and evaluation was performed.
[0116] <Comparative Example 4>
[0117] A test cell was produced and evaluated in the same manner as in Example 4 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0118] <Reference Example 1>
[0119] In the production of the negative electrode, a test cell was produced in the same manner as in Example 1 except that the second graphite particles were used as the first negative electrode active material, and the test cell was evaluated.
[0120] <Reference Example 2>
[0121] A test cell was produced and evaluated in the same manner as in Reference Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0122] <Reference Example 3>
[0123] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the first graphite particles and the second graphite particles were mixed at a mass ratio of 25:75 as the first negative electrode active material and the first graphite particles were used as the second negative electrode active material.
[0124] <Reference Example 4>
[0125] A test cell was produced and evaluated in the same manner as in Reference Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0126] <Reference Example 5>
[0127] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the second graphite particles were used as the first negative electrode active material and the first graphite particles and the second graphite particles were mixed at a mass ratio of 80:20 as the second negative electrode active material.
[0128] <Reference Example 6>
[0129] A test cell was produced and evaluated in the same manner as in Reference Example 1 except that lithium methanesulfonate was not added in the production of the positive electrode active material.
[0130] <Example 5-1>
[0131] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2 except that the amount of lithium methanesulfonate added was 0.1 mass % based on the total mass of the lithium-containing composite oxide.
[0132] <Example 5-2>
[0133] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2 except that the amount of lithium methanesulfonate added was 0.3 mass % relative to the total mass of the lithium-containing composite oxide.
[0134] <Example 5-3>
[0135] In the preparation of the positive electrode active material, a test cell was prepared and evaluated in the same manner as in Example 2 except that the amount of lithium methanesulfonate added was 1 mass % relative to the total mass of the lithium-containing composite oxide.
[0136] <Example 5-4>
[0137] A test cell was produced and evaluated in the same manner as in Example 2 except that sodium methanesulfonate was used instead of lithium methanesulfonate in the production of the positive electrode active material.
[0138] <Example 5-5>
[0139] A test cell was produced and evaluated in the same manner as in Example 2 except that lithium ethanesulfonate was used instead of lithium methanesulfonate in the production of the positive electrode active material.
[0140] <Comparative Example 5-1>
[0141] A test cell was prepared and evaluated in the same manner as in Example 2 except that lithium succinate was used instead of methanesulfonic acid in the preparation of the positive electrode active material.
[0142] <Comparative Example 5-2>
[0143] A test cell was prepared and evaluated in the same manner as in Example 2 except that lithium oxalate was used instead of methanesulfonic acid in the preparation of the positive electrode active material.
[0144] <Example 6-1>
[0145] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry to the second negative electrode mixture slurry was 10:90. The value of T1 / (T1+T2) was 0.1.
[0146] <Example 6-2>
[0147] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry and the second negative electrode mixture slurry was 25:75. The value of T1 / (T1+T2) was 0.25.
[0148] <Example 6-3>
[0149] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry and the second negative electrode mixture slurry was 75:25. The value of T1 / (T1+T2) was 0.75.
[0150] <Example 6-4>
[0151] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry and the second negative electrode mixture slurry was set to 90:10. The value of T1 / (T1+T2) was 0.9.
[0152] <Comparative Example 6-1>
[0153] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry to the second negative electrode mixture slurry was 5:95. The value of T1 / (T1+T2) was 0.05.
[0154] <Comparative Example 6-2>
[0155] In the preparation of the negative electrode, a test cell was prepared and evaluated in the same manner as in Example 1 except that the coating mass ratio per unit area of the first negative electrode mixture slurry to the second negative electrode mixture slurry was 95:5. The value of T1 / (T1+T2) was 0.95.
[0156] The evaluation results of the test battery cells of the embodiments, comparative examples and reference examples are shown in Tables 1 to 3. In Table 1, the initial discharge capacity of the test battery cells of embodiments 1 to 4 is a relative value when the initial discharge capacity of the test battery cells of comparative examples 1 to 4 is set to 100. In addition, the initial discharge capacity of the test battery cells of reference examples 1, 3, and 5 is a relative value when the initial discharge capacity of the test battery cells of reference examples 2, 4, and 6 is set to 100. In Table 2, the initial discharge capacity of the test battery cells of embodiments 5-1 to 5-5 and comparative examples 5-1 and 5-2 is a relative value when the initial discharge capacity and capacity retention rate of the test battery cell of comparative example 2 are set to 100. In Table 3, the initial discharge capacity of the test battery cells of embodiments 2, 6-1 to 6-4 and comparative examples 6-1 to 6-2 is a relative value when the initial discharge capacity of the test battery cell of comparative example 2 is set to 100.
[0157] [Table 1]
[0158]
[0159] [Table 2]
[0160]
[0161] [Table 3]
[0162]
[0163] In Tables 1 and 2, the test battery cells of the embodiments have larger initial discharge capacities than the test battery cells of the corresponding comparative examples, and the capacity retention rate is improved. From the results of Reference Examples 1-6 in Table 1, it can be seen that the capacity retention rate cannot be improved when C1<C2 is not satisfied. In addition, from the results of Comparative Examples 5-1 and 5-2 in Table 2, it can be seen that sulfonic acid compounds have a significant effect compared with succinic acid compounds and oxalic acid compounds. From the results of Comparative Examples 6-1 and 6-2 in Table 3, it can be seen that the capacity retention rate deteriorates when 0.1≤T1 / (T1+T2)≤0.9 is not satisfied.
[0164] The present disclosure is further illustrated by the following embodiments.
[0165] Composition 1:
[0166] A non-aqueous electrolyte secondary battery comprises a positive electrode, a negative electrode and a non-aqueous electrolyte.
[0167] The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide.
[0168] The aforementioned sulfonic acid compound is a compound represented by formula (I),
[0169] The negative electrode comprises a negative electrode core and a negative electrode mixture layer disposed on a surface of the negative electrode core.
[0170] The negative electrode mixture layer comprises first graphite particles having an internal porosity of 5% or less, and second graphite particles having an internal porosity of 8% or more and 20% or less, and the negative electrode mixture layer comprises a first negative electrode mixture layer opposite to the negative electrode core, and a second negative electrode mixture layer opposite to the positive electrode.
[0171] The thickness T1 of the first negative electrode mixture layer and the thickness T2 of the second negative electrode mixture layer satisfy 0.1≤T1 / (T1+T2)≤0.9,
[0172] A ratio C1 of the first graphite particles in the first negative electrode mixture layer relative to the total mass of the first graphite particles and the second graphite particles, and a ratio C2 of the first graphite particles in the second negative electrode mixture layer relative to the total mass of the first graphite particles and the second graphite particles satisfy C1<C2.
[0173]
[0174] (In formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.)
[0175] Composition: 2
[0176] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is a Group 1 element.
[0177] Composition: 3
[0178] The nonaqueous electrolyte secondary battery according to Configuration 1, wherein A is Li.
[0179] Composition: 4
[0180] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is an alkyl group.
[0181] Composition: 5
[0182] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 3, wherein R is a methyl group.
[0183] Composition: 6
[0184] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 5, wherein the amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
[0185] Composition: 7
[0186] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 6, wherein the lithium-containing composite oxide has a layered rock salt structure.
[0187] Composition: 8
[0188] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 7, wherein C1 satisfies 20 mass % ≤ C1 ≤ 100 mass %.
[0189] Composition: 9
[0190] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 8, wherein T1 and T2 satisfy 0.5≤T1 / (T1+T2)≤0.75.
[0191] Composition: 10
[0192] The nonaqueous electrolyte secondary battery according to any one of Configurations 1 to 9, wherein at least a portion of the surface of the first graphite particles is covered with amorphous carbon.
[0193] Description of Reference Numerals
[0194] 10 non-aqueous electrolyte secondary battery, 11 positive electrode, 12 negative electrode, 13 separator, 14 electrode body, 16 outer can, 17 sealing body, 18, 19 insulating plate, 20 positive electrode lead, 21 negative electrode lead, 22 groove portion, 23 internal terminal plate, 24 lower valve body, 25 insulating member, 26 upper valve body, 27 cover, 28 gasket, 30 negative electrode core, 32 negative electrode mixture layer, 32a first negative electrode mixture layer, 32b second negative electrode mixture layer, 40 graphite particles, 42 internal pores, 44 external pores.
Claims
1. A non-aqueous electrolyte secondary battery comprising a positive electrode, a negative electrode and a non-aqueous electrolyte, The positive electrode comprises a lithium-containing composite oxide and a sulfonic acid compound present on the surface of particles of the lithium-containing composite oxide. The sulfonic acid compound is a compound represented by formula (I), The negative electrode includes a negative electrode core and a negative electrode mixture layer disposed on a surface of the negative electrode core. The negative electrode mixture layer includes first graphite particles having an internal porosity of 5% or less, and second graphite particles having an internal porosity of 8% or more and 20% or less, and the negative electrode mixture layer includes a first negative electrode mixture layer facing the negative electrode core, and a second negative electrode mixture layer facing the positive electrode. The thickness T1 of the first negative electrode mixture layer and the thickness T2 of the second negative electrode mixture layer satisfy 0.1≤T1 / (T1+T2)≤0.9, A ratio C1 of the first graphite particles in the first negative electrode mixture layer to the total mass of the first graphite particles and the second graphite particles, and a ratio C2 of the first graphite particles in the second negative electrode mixture layer to the total mass of the first graphite particles and the second graphite particles satisfy C1<C2, In formula (I), A is a Group 1 or Group 2 element, R is a hydrocarbon group, and n is 1 or 2.
2. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is a Group 1 element.
3. The nonaqueous electrolyte secondary battery according to claim 1, wherein The A is Li.
4. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is an alkyl group.
5. The nonaqueous electrolyte secondary battery according to claim 1, wherein The R is a methyl group.
6. The nonaqueous electrolyte secondary battery according to claim 1, wherein An amount of the sulfonic acid compound present on the surface of the lithium-containing composite oxide is 0.1 mass % or more and 1 mass % or less relative to the mass of the lithium-containing composite oxide.
7. The nonaqueous electrolyte secondary battery according to claim 1, wherein The lithium-containing composite oxide has a layered rock salt structure.
8. The nonaqueous electrolyte secondary battery according to claim 1, wherein The C1 satisfies 20 mass % ≤ C1 ≤ 100 mass %.
9. The nonaqueous electrolyte secondary battery according to claim 1, wherein The T1 and the T2 satisfy 0.5≤T1 / (T1+T2)≤0.
75.
10. The nonaqueous electrolyte secondary battery according to claim 1, wherein At least a portion of the surface of the first graphite particles is covered with amorphous carbon.
Citation Information
Patent Citations
Lithium titanate powder for power storage device electrode, active substance material, and power storage device using the active substance material
JP2018006164A